Factors Associated with Farmers’ Perception towards Climate Change in Pokhara - Dhungana, Ananta Raj (Janapriya Journal of Interdisciplinary Studies, 2018)
Climate change is one of the major concerns among the researchers in twenty first century. This study aims to analyze the factors associated with farmers’ perception towards climate change in Pokhara. For this purpose, two wards of Pokhara i.e. ward no. 30 and ward no. 33 were selected purposively. Out of 3982 households in these wards, 216 households are proportionately distributed in these wards. Information was collected by using structured questionnaire through interview techniques with household head or a household member having age 40 years and over and residing in that locality since last 10 years. A systematic sampling technique was carried out to select the samples. Chi-squared test was applied to find the factors associated with farmers’ perception towards climate change. All the respondents were aware about the climate change and received information about climate change from radio, television, newspaper, peer groups. Majority of the respondents claim that climate change has been occurred in temperature, annual summer hotness, decrease in average annual rainfall, no change in average annual draught incidents, no change in flood incidents, no change in water availability to irrigate and increase in average number of pest and plant disease attack. It is found that there is significant association between farmer’s perception level towards climate change with agriculture skill of the respondents, caste/ethnicity, major occupation and sex. Hence agriculture skill, sex, caste/ethnicity and occupations of the respondents are the major factors associated with farmers’ perception towards climate change.